2018
DOI: 10.31224/osf.io/ntfdp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Drive-by Health Monitoring to Detect Bridge Damage Considering Environmental and Operational Effects

Abstract: Drive-by Health Monitoring utilizes accelerometers mounted on vehicles to gather dynamic response data that can be used to continuously evaluate the health of bridges faster and with less equipment than traditional structural health monitoring practices. Because vehicles and bridges create a coupled system, vehicle acceleration data contains information about bridge frequencies that can be used as health indicators. However, for drive-by health monitoring to be viable, variabilities in dynamic measurements cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A research gap identified by them that needs to be addressed to improve the effectiveness of drive-by monitoring is the effect that road roughness has on indirect monitoring. More recently, Locke et al (2020) present a drive-by monitoring approach capable of not only considering road roughness, which is modeled based on power spectral density functions (International Organization for Standardization, 2016), but also variable environmental and operational conditions.…”
Section: Bhm Ai and Adasmentioning
confidence: 99%
“…A research gap identified by them that needs to be addressed to improve the effectiveness of drive-by monitoring is the effect that road roughness has on indirect monitoring. More recently, Locke et al (2020) present a drive-by monitoring approach capable of not only considering road roughness, which is modeled based on power spectral density functions (International Organization for Standardization, 2016), but also variable environmental and operational conditions.…”
Section: Bhm Ai and Adasmentioning
confidence: 99%